Parental willingness to pay the cervical cancer vaccination cost of senior high school aged students in Badung District - Ni Ketut Karneli; Ketut Suwiyoga; I Gede Adnyana Sudibya (Public Health and Preventive Medicine Archive, 2013)
The incidence of cervical cancer is high in Bali (0.8%), and more than 70% of cases are detected at an advanced stage (above 2B), making it difficult to treat. Prevention efforts are still very low; the Badung District only financed 1567 vaccinations from 8784 senior high school students, accounting for around 17.8%. Vaccination requires substantial funds, and its sustainability required community participation. This cross-sectional study aims to determine the relationship between the variables of perceived susceptibility, perceived severity, perceived benefits, perceived barriers, education and employment with the willingness of the parents to cover the costs of vaccination. A study was conducted using 196 samples from 595 populations selected by systematic random sampling, consisting of mothers of grade one high school students at SMU Petang, SMU 2 Mengwi, and SMU 1 North Kuta. The data was obtained through self-administered questionnaires. Perceived benefits and severity were measured by assessing the answers to open questions and pre-coded. Chi square and logistic regression tests were applied when analyzing the data. The results of the analysis show that willingness of parents to cover the cost is still low (43%) with 70% of respondents willing to pay less than Rp. 237,500 for three doses. Bivariate analysis found that: perceived susceptibility [RP=1,31; 95%CI: 1,04-1,67], perceived severity [RP=1,57; 95%CI: 1,20-2,05], perceived benefits [RP=1,84; 95%CI: 1,39-2,45], education [RP=1,64; 95%CI: 1,05-2,57], perceived barriers [RP=0,89; 95%CI: 0,70-1,15] and occupation [RP=1,18; 95%CI: 0,87-1,60]. From the results it can be concluded that the perceived susceptibility, perceived severity, perceived benefits and education are related to the willingness of the parents to cover vaccine costs, however, perceived barriers and occupation were not shown to be associated. The related dominant factor is perceived benefits. It is suggested that health promotion should emphasise on the benefits of the vaccination and cervical cancer malignancy rates in order to increase people's willingness to cover cervical cancer vaccination costs.